Semiologic, electroencephalographic and electrocardiographic correlates of seizure-like manifestations caused by cardiac asystole. (July 2015) - Jackson, Anvesh; Bower, Simon; Seneviratne, Udaya
Highlights: Cardiac asystole can be associated with clinical manifestations mimicking seizures. Seizure-mimics occur in three phases: pre-asystole, cerebral hypoperfusion and reperfusion. Early pallor, rapid breathing and late flushing are useful in the diagnosis. EEG illustrates typical "slow-flat-slow" pattern during clinical events. Early recognition of this condition is important to avoid inappropriate treatment. Abstract: Purpose: Cardiac asystole is known to cause clinical manifestations mimicking seizures. The recognition of this uncommon phenomenon is important to expedite appropriate clinical intervention and avoid unnecessary morbidity as well as potential mortality. Methods: We retrospectively reviewed video-electroencephalographic (EEG) records from January 2008 to December 2013 for relevant cases. Results: We identified four patients who experienced nine events of asystole accompanied by seizure-like activity captured on video-EEG. None had evidence of epilepsy on video-EEG. Semiological features of captured clinical events included aura, automatisms, generalized tonic activity and focal as well as generalized myoclonus. No patient had generalized tonic-clonic seizures. A peculiar rapid breathing pattern was seen preceding the onset of asystole. General pallor was observed during asystole, followed by flushing on recovery. Seizure-like semiology was observed in three stages; pre-asystole, during asystole and after resumption of cardiac rhythm. The EEG demonstrated generalized slowing followed by generalized suppression during asystole and generalized slowing again on resumption of sinus rhythm ("slow-flat-slow" pattern). All patients had dual-chamber pacemakers implanted. On follow-up, they have remained symptom-free without antiepileptic medications. Conclusions: Cardiac asystole can be associated with features closely mimicking seizures. Recurrent episodes of cardiac asystole can be stereotypical in a given patient. There are some diagnostic clues in semiology.